2007
DOI: 10.1002/dneu.20532
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic plasticity and associative learning are impaired in a Drosophila presenilin null mutant

Abstract: Alzheimer's disease is a neurodegenerative disorder characterized by progressive memory and cognitive decline that is associated with changes in synaptic plasticity and neuronal cell loss. Recent evidence suggests that some of these defects may be due to a loss of normal presenilin activity. Here, we have examined the effect of loss of Drosophila presenilin (psn) function on synaptic plasticity and learning. Basal transmitter release was elevated in psn mutants while both paired pulse synaptic plasticity and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 60 publications
(78 reference statements)
5
24
0
Order By: Relevance
“…Recently, several labs have shown that mutations for genes that model aspects of Alzheimer’s disease are deficient in olfactory conditioning. Deficits have been found in flies carrying an artificial mutation in human amyloid-b-42 , flies mutant for presenilin and flies expressing a wild-type version of the microtubule associated protein Tau ( UAS - Tau wt ), to name a few (Iijima et al 2008; Knight et al 2007; Mershin et al 2004). Interestingly, the learning deficits frequently precede other signs of pathology (Iijima et al 2008; Mershin et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several labs have shown that mutations for genes that model aspects of Alzheimer’s disease are deficient in olfactory conditioning. Deficits have been found in flies carrying an artificial mutation in human amyloid-b-42 , flies mutant for presenilin and flies expressing a wild-type version of the microtubule associated protein Tau ( UAS - Tau wt ), to name a few (Iijima et al 2008; Knight et al 2007; Mershin et al 2004). Interestingly, the learning deficits frequently precede other signs of pathology (Iijima et al 2008; Mershin et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…To test this possibility, we examined a different form of short-term plasticity, specifically, posttetanic potentiation (PTP). Previous studies have shown that EJP amplitudes are transiently elevated after a brief tetanic stimulation (Zhong and Wu, 1991;Knight et al, 2007). We compared the EJP amplitudes during a 0.2 Hz train of stimuli before and after a brief tetanic stimulation (30 s; 10 Hz).…”
Section: Synaptic Strength and Plasticity Are Impaired In Ent2 Mutantsmentioning
confidence: 99%
“…Another group has also observed that PS1 deficiency increases synaptic release and affects the number and docking of synaptic vesicles [69]. It was also shown that basal transmitter release was increased at the neuro-muscular junction in Drosophila lacking PS expression [73]. However, even though basal synaptic transmission seems to be intensified in this later model, synaptic strength and plasticity were impaired after posttetanic potentiation [73].…”
Section: Ps and Cellular Substrates Of Memorymentioning
confidence: 99%
“…It was also shown that basal transmitter release was increased at the neuro-muscular junction in Drosophila lacking PS expression [73]. However, even though basal synaptic transmission seems to be intensified in this later model, synaptic strength and plasticity were impaired after posttetanic potentiation [73]. As a likely consequence, associative learning ability was also impaired.…”
Section: Ps and Cellular Substrates Of Memorymentioning
confidence: 99%